Effect of Cryptocurrency Marketplace Incentive Distribution with Burning Token Method on Halal Crypto Exchange Token Value - Rendy Ardiansyah; Ibnu Khajar (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
At the beginning of the 21st century, one of the most in-demand technology investments was blockchain/cryptocurrency technology. Cryptocurrency usage globally has increased from 106 million in January 2021 to 295 million users in December 2021 or an increase of 178% in 2021. The world market capitalization value of cryptocurrency has increased from 787 billion dollars in January 2021 to 2.3 trillion dollars in December 2021 or an increase of 192% in 2021. In the Cryptocurrency world, one method of sharing incentives is to "burn" tokens, namely using dividend allocations to be used to buy back cryptocurrencies and reduce the supply of circulating tokens. This is different from stock investment, namely the distribution of incentives through cash. This paper aims to develop a conceptual model of the Cryptocurrency Marketplace incentive distribution model in the form of "burn" tokens against the Halal Crypto Exchange Token.